The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/eqe.2231
|View full text |Cite
|
Sign up to set email alerts
|

Development of earthquake vulnerability functions for tall buildings

Abstract: SUMMARY This study focuses on the development of vulnerability functions for tall buildings. A systematic simulation approach based on the Pacific Earthquake Engineering Research loss assessment framework is used to develop building vulnerability functions that provide estimates of losses to buildings under ground motions of various intensities. The steps involved in the procedure are: quantifying ground‐motion hazard using a vector of spectral accelerations; predicting building response parameters such as sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 11 publications
(15 reference statements)
0
24
0
Order By: Relevance
“…Then, depending on the desired level of accuracy and simplicity, appropriate structural analysis methods are employed, typically based on either nonlinear static analysis (e.g., capacity-spectrum [17,31,32], displacement-based methods [33,34], etc.) or nonlinear dynamic analysis [19,21,35,36]. In both cases, a major issue is the invariance of a building's (or classof-buildings') vulnerability/fragility function from the site itself.…”
Section: Introductionmentioning
confidence: 99%
“…Then, depending on the desired level of accuracy and simplicity, appropriate structural analysis methods are employed, typically based on either nonlinear static analysis (e.g., capacity-spectrum [17,31,32], displacement-based methods [33,34], etc.) or nonlinear dynamic analysis [19,21,35,36]. In both cases, a major issue is the invariance of a building's (or classof-buildings') vulnerability/fragility function from the site itself.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a recent study by AIR Worldwide [5] suggested that regional economic loss associated with a hypothetical M w 9 Cascadia earthquake scenario can be significant.An accurate assessment of potential impact of future destructive earthquakes is essential for effective disaster risk reduction and requires decision-support tools that facilitate the quantitative seismic loss estimation. Probabilistic seismic risk analysis (PSRA) entails comprehensive understanding of ground shaking information, such as fault rupture process, wave propagation, and site effects, as well as vulnerability of structures, such as structural damage accumulation, seismic loss generation, and societal/economic impact [6][7][8]. Through probabilistic calculus, PSRA evaluates the potential damage and loss that a certain group of structures is likely to experience because of various seismic events.A seismic demand model characterizes a probabilistic relationship between seismic intensity measure (IM) and engineering demand parameter (EDP).…”
mentioning
confidence: 99%
“…These were computed following the building-specific storey-based loss estimation methodology proposed by Ramirez et al [21], considering the effect of demolition-related losses [22]. In order to compute the demolition-related losses, the probability of demolition given a residual ISDR, P(D|RISDR), was assumed to follow a lognormal distribution with a median of 1.85% and a logarithmic standard deviation of 0.3 [23]. To what pertains the repair losses, the structural damage fragility curves proposed in HAZUS [24] for high-code steel braced frames were used, in conjunction with the repair cost ratios proposed in HAZUS for multifamily dwellings.…”
Section: Earthquake-induced Riskmentioning
confidence: 99%